Evaluation of Free Radical Scavenging Activity in Ethanolic Extract from Promising Accessions of Curcuma aeruginosa RoxB. - Waras Nurcholis; Nurul Khumaida; Muhamad Syukur; Maria Bintang (Molekul, 2017)
This study evaluated the free radical scavenging activity in ethanolic extracts from 20 accessions of Curcuma aeruginosa. The radical scavenging activity of the extract accessions was investigated with 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical. IC50 values for DPPH radical scavenging activity ranged from 89.81 to 505.65 µg mL-1. Based on IC50 values, twenty accessions of C. aeruginosa can be divided into three groups: strong (two accessions); moderate (seventeen accessions); and low (one accession) of DPPH scavenger. Sukoharjo (SH) and Muara Bungo (MB) showed promising accessions for antioxidant potential, thus these accessions important to selection for future breeding program in pharmaceutical products.